STABILITY OF REDUCED POLYPYRROLE - KIM, DY; LEE, JY; MOON, DK; KIM, CY (ELSEVIER SCIENCE SA LAUSANNE, 1995)
Electrochemically polymerized polypyrrole(PPy) shows changes in visible light spectrum during electrochemical reduction revealing changes in electron states of the conjugated double bond. The concentration of polarons increases fast in the early stage during reduction on expense of bipolarons but drops off momentarily to show an increase of bipolaron concentration which again decreases with further reduction. The reduced PPy is unstable to show changes in the visible light spectrum in less than one minute after cutting off applied potential. The absorption peak at 420nm assigned as pi-pi* transition in the conjugated double bond shrinks fast to show a strong absorption around 800nm assigned as bipolaron. It is observed that the spectral changes slow down when hydroquinone is added to the system. The addition of hydroquinone in the system stabilizes polaron not to couple with each other during natural oxidation of PPy and makes the polymer segments not to turn easily into a bipolaron state from a polaron state. Hydroquinone is oxidized in an aqueous system to produce protons which seem to stabilize free radicals in the polaron state. It is suggested that deprotonation of -N+H in the pyrrole ring develops into production of an imine structure to loose the electrochemical reactivity.
Keywords: POLYMERS